Enhancement in greenish-white photoluminescence of Zn3(VO4)2 phosphor by Bi3+ doping - Chauhan V.; Dixit P.; Pandey P.C. (My University, 2025)
In this paper, we have explored the photoluminescence properties of rare-earth free Zn(3-x)Bix(VO4)2 (x = 0, 0.01, 0.03, 0.05) phosphors, synthesized by solution combustion method. The Rietveld refinement confirms that the prepared phosphors have an orthorhombic phase. The Bi3+ doping in the host supports the crystallite growth and reduction of microstrain. The absorption study ascertains the shift in the absorption edge with Bi3+ doping. The lowering of Urbach energy with Bi3+ doping in the host confirms the improvement of crystallinity. The prepared phosphors have near-Ultraviolet (UV) excitation of 350 nm, which reduces visible light reabsorption. The host has broadband emission centered on 540 nm and is enhanced by the factor of 11 after 1% doping of Bi3+ ions. The emission enhancement is attributed to the improved crystallinity and reduced microstrain. Thus, Bi3+ doped Zn3(VO4)2 phosphor can be used as a greenish-white emission source for optical devices. © 2021 Elsevier GmbH